Outcome-Based Teaching and Learning (OBTL) Practices of the Coast Guard Special Operations Force (CGSOF) Specialization Courses - Torres Jr., Noli C (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The goal of outcome-based teaching and learning, or OBTL, is to provide students with explicit instructions on what they are expected to learn and how to demonstrate that learning before any instruction even begins. While the idea behind OBTL has been around for a while, the Philippine Coast Guard (PCG) has just lately included it in its training curriculum. The Coast Guard Special Operations Force (CGSOF), one of the PCG's operating units, is dedicated to integrating OBTL into its system through its training institute in order to address the current trend in education. Determining the degree of OBTL practice implementation in the CGSOF-led specialized courses is the primary goal of the research. This study used a mixed-methods research approach that used quantitative and qualitative techniques. mixed-methods research design where survey questionnaires and informal interviews were used in data gathering. There were 42 instructors and 130 trainees from the CGSOF included in the study. The findings revealed that both the instructors’ self-assessment and the trainees’ observation showed a significant extent in the implementation of OBTL practices. There is a substantial alignment between the measurable competencies that trainees should exhibit at the end of the course with respect to its three main components: the intended learning outcomes (ILOs), teaching and learning activities (TLAs), and assessment tasks (ATs). Despite several identified factors affecting the OBTL implementation, including the lack of equipment and training facilities that most affect the alignment of the ILOs, TLAs, and ATs, it was still indicated that the implementation of OBTL in the CGSOF specialization courses has been applied with a consistently high degree of satisfaction and efficacy, offering instructors and trainees a well-rounded education experience.